1997
DOI: 10.1097/00005537-199707000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of Caustic Hair Relaxer: Is Endoscopy Necessary?

Abstract: Hair relaxer, a commercially available alkaline product, is commonly the offending agent in caustic ingestion. These patients often experience oral cavity and facial burns; however, no clinically significant esophageal injuries have been reported. Therefore, we questioned the therapeutic and economic efficacy of the "standard treatment protocol" that includes hospitalization and endoscopic evaluation. Twenty-six patients over a 7-year period presented to our institution having ingested hair relaxer. Presenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 19 publications
4
18
0
Order By: Relevance
“…On the other hand, endoscopy is not recommended in asymptomatic children, especially in developed countries where the likelihood of severe esophageal burns is low. 9,15,21,26 In our study, the use of the criteria for endoscopy proposed by previous authors 19,21 resulted in the reduction of the patients who underwent endoscopy, whereas no case with severe tissue injury (grade II and III esophageal burns and gastric damage) was missed. All children who did not meet the criteria for endoscopy and were not subjected to this procedure had an uncomplicated clinical course.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…On the other hand, endoscopy is not recommended in asymptomatic children, especially in developed countries where the likelihood of severe esophageal burns is low. 9,15,21,26 In our study, the use of the criteria for endoscopy proposed by previous authors 19,21 resulted in the reduction of the patients who underwent endoscopy, whereas no case with severe tissue injury (grade II and III esophageal burns and gastric damage) was missed. All children who did not meet the criteria for endoscopy and were not subjected to this procedure had an uncomplicated clinical course.…”
Section: Discussionmentioning
confidence: 54%
“…Most authors agree that endoscopy is warranted in all symptomatic children, in order to assess the severity of esophageal and gastric injuries. On the other hand, endoscopy is not recommended in asymptomatic children, especially in developed countries where the likelihood of severe esophageal burns is low 9,15,21,26 …”
Section: Discussionmentioning
confidence: 99%
“…33 When compared with untreated hair, Syed et al 36 found the tensile strength of chemically treated hair to be lower, with an associated increase in porosity, indicating damage. Khumalo et al 39 also found the cysteine levels of chemically relaxed afro-textured hair to be lower than that of natural hair. In particular, the cysteine content of distal chemically relaxed hair was similar to those found in patients with Trichothiodystrophy (TTD), a genodermatoses characterized by the presence of brittle fragile hair.…”
Section: Chemical Relaxersmentioning
confidence: 97%
“…found the tensile strength of chemically treated hair to be lower, with an associated increase in porosity, indicating damage. Khumalo et al . also found the cysteine levels of chemically relaxed afro‐textured hair to be lower than that of natural hair.…”
Section: Chemical Straightening Of Afro‐textured Hair; Clinical Aspectsmentioning
confidence: 98%
See 1 more Smart Citation